The Sun Rises on the Solar Sector - Ahmad, Reyaz A. (World Bank, Washington, DC, 2012)
Energy from the sun is abundant and free. Solar energy is in essence electromagnetic radiation emitted from the sun. Earth's climate, hydrologic systems, and ecosystems all derive from the sun. Other forms of renewable power such as wind, wave, biomass, and hydro are an indirect function of solar radiation.